The larva and pupa of Anabolia appendix (Ulmer 1905) (Trichoptera: Limnephilidae) from China - Deng, Zhen; Zang, Haoming; Wang, Meng; Sun, Changhai (Zootaxa, 2024)
Adult females from the town of Xin-si, Ding-xi County, Gan-su Province, as well as larvae and pupae from Tian-jun and Qi-lian Counties, Hai-bei Tibetan Autonomous Prefecture, Qing-hai Province, were examined, and their COI sequences were extracted and analyzed. Adult females were identified as Anabolia appendix (Ulmer 1905) and were associated with larvae and pupae by their COI sequences. The larva and pupa of A. appendix are described and diagnosed for the first time and morphological photos of the larva and pupa of A. appendix are also provided. All the COI sequences have been uploaded to GenBank. All specimens are deposited in the Insect Collection, Nan-jing Agricultural University, Nan-jing, Jiang-su Province, P. R. China.